Development and Validation of a Five-Tier Diagnostic Test for Identifying High School Students' Misconceptions in Static Fluid Concepts - Muhammad Roihan Ilham; Handjoko Permana; Vina Bekti Utami (Universitas Negeri Makassar, 2026)
This study developed a valid and feasible five-tier diagnostic test for identifying high school students’ misconceptions in static fluids. Conventional assessment instruments often have difficulty distinguishing conceptual errors from answers produced through random guessing. The study adopted a Research and Development (R&D) approach using the 4D model, which was limited to the define, design, and develop stages because of time constraints. A total of 63 eleventh-grade students were selected through convenience sampling, including 28 students for empirical testing and 35 students for instrument implementation. Expert appraisal resulted in a very high level of content validity, as indicated by an Aiken’s V coefficient of 0.956, while the physics teacher assessment produced a feasibility score of 89.06%, confirming that the instrument was highly suitable for classroom use. The empirical test retained 28 valid items with very high internal consistency, reflected in a Cronbach’s alpha coefficient of 0.943, and discrimination indices ranging from 0.200 to 0.775. The implementation results showed that Conceptual Understanding was the dominant profile at 46.22%. However, Misconceptions were still identified in 10.91% of the responses, with the highest rate occurring in Archimedes’ principle at 19.34%. Compared with existing four-tier diagnostic tests, the main contribution of this instrument lies in its open-ended fifth tier, which helps minimize lucky-guess responses and provides clearer evidence of students’ physical reasoning. Therefore, the instrument offers a more detailed means of identifying students' cognitive obstacles and provides teachers with a stronger basis for designing targeted remedial instruction.